2013
DOI: 10.1590/s0102-05362013000200011
|View full text |Cite
|
Sign up to set email alerts
|

Concentração dos sais e da sacarose do meio MS na multiplicação in vitro e na aclimatização de batata

Abstract: Palavras-chave: Solanum tuberosum, sobrevivência ex vitro, produção de mudas, propagação vegetativa. ABSTRACTMS salt and sucrose concentrations in the in vitro multiplication and acclimatization of potato

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
0
15
0
3
Order By: Relevance
“…The clonal mini-hedge was established in polyethylene trays, placed in a greenhouse and fertirrigated as described in BANDINELLI et al (2013) For clonal mini-hedge formation, oneyear-old seedlings (seminal origin) and plantlets (rooted cuttings) were transplanted to the growing beds of the polyethylene trays. After 10 days of cultivation, they were pruned at 6.0cm height to get the ministumps, which provided the sprouts to prepare the mini-cuttings.…”
Section: O Objetivo Deste Trabalho Foi Avaliar a Produtividade De Minmentioning
confidence: 99%
“…The clonal mini-hedge was established in polyethylene trays, placed in a greenhouse and fertirrigated as described in BANDINELLI et al (2013) For clonal mini-hedge formation, oneyear-old seedlings (seminal origin) and plantlets (rooted cuttings) were transplanted to the growing beds of the polyethylene trays. After 10 days of cultivation, they were pruned at 6.0cm height to get the ministumps, which provided the sprouts to prepare the mini-cuttings.…”
Section: O Objetivo Deste Trabalho Foi Avaliar a Produtividade De Minmentioning
confidence: 99%
“…It is important to emphasize that these results corroborate the present study for the same evaluated characteristics, showing that plants from the Zingiberaceae family tend to respond positively to an increase in sucrose concentration in the culture medium. Different results were obtained for two species of S. tuberosum, which increase in sucrose concentration limited the number of leaves and the length of the aerial part of in vitro seedlings (Bandinelli et al, 2013). In Orbignya oleifera embryos, the interaction between sucrose and activated charcoal was not significant.…”
Section: Effect Of Activated Charcoal and Sucrosementioning
confidence: 78%
“…Moreover, some species such as Ocimum basilicum are frequently intolerant to high salt concentrations in the range of (70 to 100%) (Tarchoune et al, 2012). Species with concentration lower than 70% have been more favorable to the development and with regard to Solanum tuberosum where 50% of the MS medium salts caused vigorous and health seedlings (Bandinelli et al, 2013). As reported by Islam et al (2004), a 75% salt concentration was more important for induction of microrhizomes in turmeric than was treatment with 100% salt concentration.…”
Section: Introductionmentioning
confidence: 99%
“…In potato plants cultured in vitro, Bandinelli et al (2013) observed that the increase of sucrose concentration in the MS medium was accompanied by a decrease in the biomass production. The dynamics of solute translocation in the phloem helps to explain the reduction in the height of seedlings cultured in medium with higher concentrations of sucrose.…”
Section: Resultsmentioning
confidence: 99%